Design and fabrication of an on-farm multipurpose cabinet dryer - Okafor Izuchukwu John; Olanrewaju John Seye; Obiakor Sylvester Chukwujekwu; Ojukwu Enyeluibe Onyukwu; Tsee Andrew Ternenge; Willoughby Fouad Ayinde; Okoro Uchenna Peter; Oyedokun Jelili Aremu (Journal on Processing and Energy in Agriculture, 2024)
The design and fabrication of an on-farm multipurpose cabinet dryer were carried out to address the drying needs of small and medium-scale farmers by providing an efficient, mobile, and sustainable solution for post-harvest processing. The dryer operates with a required air volume of 31.8 m³/min, powered by a blower with a speed of 36,083 rpm, a pressure coefficient of 0.65, and a flow coefficient of 0.69, requiring 162 kW of power input. Heat transfer calculations indicated conduction heat transfer of 21,600 W/m.K, convection at 5.8 x 10⁵ W/m².K, and radiation at 1.85 x 10²¹ W/m², with an overall heat transfer coefficient of 1.85 x 10²¹ W/m².K. The energy source for the dryer is solid fuel, and the design incorporates a lagged drying chamber to minimize heat loss. A fan is mounted on top of the chamber for regulated exhaust of humid air, while solar power operates the fans for energy efficiency. Mobility is enhanced through two wheels, and the blower is connected to the heat exchanger through a frustum-shaped vacuum to ensure even air distribution. Key considerations included the availability of materials, cost, and durability, resulting in an efficient, cost-effective, and sustainable drying solution suitable for on-farm and off-farm operations. This dryer is expected to significantly improve crop drying processes, enhance productivity, and reduce post-harvest losses.